On the Principles of Resource Consumption Optimization on Microeconomic Level - Petru Stefea; Andrei Pelin (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
In a business environment defined by overproduction, ever increasing competitive pressures, fast technological dynamics, there remain few reliable instruments to be used by managers in order to develop and maintain competitive advantages. Traditionally, manufacturing cost reduction represents one the solution that are most close to the managers in order to counteract the threats coming from a business's environment. In such a context, this paper aims to develop the ways to obtain cost reduction of three types of resources: direct materials, direct labour and manufacturing overhead. The main method used in the article is analytical logic, the objective being to highlight the approaches to be used in order to optimize resource consumption in its different forms. The results of the article focus on the practical ways to increase a manufacturing enterprise's efficiency.
Keywords: M21; D24; 330; Cost optimization; resource consumption efficiency; cost reduction; direct costs; overhead